Comparative Efficacy of Pharmacotherapy for Macular Edema Secondary to Retinal Vein Occlusion: A Network Meta-analysis - Gao, Sheng; Zhang, Yun; Li, Xun; Ge, Ge; Duan, Jianan; Lei, Chunyan; Zeng, Yue; Cai, Zhaolun; Zhang, Meixia (Frontiers in Pharmacology, 2021)
Purpose: This network meta-analysis was conducted to obtain the relative effectiveness of different pharmacotherapy of macular edema secondary to retinal vein occlusion (RVO) by summarizing all available evidences. Methods: PubMed, Embase, and Cochrane Library databases were searched for all relevant randomized controlled trials. The outcomes were estimated through a network meta-analysis, including the mean change in best-corrected visual acuity (BCVA) from baseline, the proportion of patients who gained ≥15 letters in BCVA from baseline, the mean change in central retinal thickness (CRT). Results: We identified 15 randomized controlled trials (RCTs) involving 3,431 patients with RVO in our study. Different therapeutic regimens were compared including three anti-vascular endothelial growth factor (VEGF) agents (ranibizumab, bevacizumab, and aflibercept), ranibizumab with laser, dexamethasone intravitreal implant, and laser. For branch RVO, ranibizumab 0.5 mg monthly [weighted mean difference (WMD) = 11, 95% confidence intervals (CrI) 3.6 to 19], ranibizumab 0.5 mg 3 + pro re nata (WMD = 9.4, 95% CrI 0.43–18) is most effective in terms of changes of BCVA and 15 letters or more of BCVA improvement. For central RVO, three anti-VEGF regimens can improve visual acuity and there is no significant difference of efficacy among ranibizumab, bevacizumab and aflibercept (p > 0.05). Ranibizumab 0.5 mg monthly could achieve additional efficacy in CRT reduction in eyes with branch RVO or central RVO (WMD = -130, 95% CrI -400 to 140 or WMD = -280, 95% CrI -590 to 16)). Dexamethasone intravitreal implant (WMD = 1.7, 95% CrI -4.2 to 7.1 or WMD = 0.38, 95% CrI -9.8 to 8.8)) did not show a significant improvement in visual acuity at the end of 6 months follow-up in eyes with branch RVO or central RVO. Conclusion: In summary, this network meta-analysis demonstrated several anti-VEGF agents had equivalent effects on mean visual acuity changes and anatomical recovery in 6 months in eyes with branch or central RVO. Only one injection of dexamethasone intravitreal implant in 6 months could not maintain the visual benefit. Patients and clinicians could choose pharmacotherapies with further consideration toward personal factors.